Anti-sperm Antibody Positivity in Men with Varicocele: A Systematic Review and Meta-Analysis - Marco Falcone; Kadir Bocu; Hakan Keskin; Jesus Fernando Solorzano Vazquez; Ravi Banthia; Tara Mahendran; Muslim Dogan Deger; Vinod Kv; Preto Mirko; Ahmed M. Harraz; Ramadan Saleh; Rupin Shah; et al. (The World Journal of Men's Health)
Purpose: Despite the significant role of varicocele in the pathogenesis of male infertility, its association with anti-sperm antibodies (ASA) remains controversial. This systematic review and meta-analysis (SRMA) aims to investigate the frequency of ASA positivity in men with varicocele. Materials and Methods: This SRMA is conducted in accordance with the Meta-analysis of Observational Studies in Epidemiology guidelines. We investigated the frequency of ASA positivity in ejaculates or serum of men with varicocele as compared to men without varicocele (controls). A literature search was performed using the Scopus and PubMed databases following the Population Exposure Comparison Outcome, Study Design model. Data extracted from eligible studies were meta-analyzed and expressed as odds ratios (ORs) and confidence intervals (CIs). Results: Out of 151 abstracts identified during the initial screening, 6 articles met the inclusion criteria and were included in the meta-analysis. Using mixed antiglobulin reaction (MAR) assay, 61 out of the 153 (39.8%) patients with varicocele tested positive for ASA in their ejaculates as compared to 22 out of the 129 control subjects (17%, OR=4.34 [95% CI: 1.09–17.28]; p=0.04). Using direct or indirect immunobead test, 30 out of 60 cases diagnosed with varicocele (50%) had shown ASA positivity in their ejaculates as compared to 16 out of 104 controls (15.4%, OR=3.57 [95% CI: 0.81–15.68]; p=0.09). Using enzyme-linked immunosorbent assay (ELISA), out of 89 varicocele patients, 33 (37.1%) tested positive for serum ASA as compared to 9 out of 57 participants in the control group (15.8%, OR=7.87 [95% CI: 2.39–25.89]; p<0.01). Conclusions: This SRMA indicates that ASA positivity is significantly higher among men with varicocele when tested by direct method (MAR) or indirect method (ELISA). This data suggests an immunological pathology in infertile men with varicocele and may have implications for the management of these patients.